1990
DOI: 10.1111/j.1476-5381.1990.tb12065.x
|View full text |Cite
|
Sign up to set email alerts
|

Role of β‐adrenoceptor‐adenylate cyclase system in the developmental decrease in sensitivity to isoprenaline in foetal and neonatal rat heart

Abstract: 1 The inotropic and chronotropic sensitivity to noradrenaline and isoprenaline (Iso) of foetal and ngonatal rat heart decreases as the heart becomes sympathetically innervated. In the present study, we have examined adenylate cyclase (AC) activation and fl-adrenoceptor binding to determine whether a developmental decrease in sensitivity was demonstrable in the fl-receptor-AC system of atrial and ventricular membranes from the 15 day foetus and 1 day and 7 day neonates. 2 While the maximum activation of AC by I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
1

Year Published

1991
1991
2015
2015

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 30 publications
(12 citation statements)
references
References 20 publications
2
9
1
Order By: Relevance
“…The calculated half-maximal effective concentration for isoprenaline in these experiments was shown to be in the lower nanomolar range, which is ϳ10-fold less than those reported from studies in neonatal rat hearts and adult rat papillary muscle [ϳ50 nM; (52,91)]. The relative isoprenaline-induced increase in force appears smaller in engineered constructs than in adult heart preparations (ϳ2-fold vs. 4 -5-fold, Table 1), which may again indicate immaturity.…”
Section: Tissue Engineering To Model (Human) Heart Tissue Functioncontrasting
confidence: 38%
“…The calculated half-maximal effective concentration for isoprenaline in these experiments was shown to be in the lower nanomolar range, which is ϳ10-fold less than those reported from studies in neonatal rat hearts and adult rat papillary muscle [ϳ50 nM; (52,91)]. The relative isoprenaline-induced increase in force appears smaller in engineered constructs than in adult heart preparations (ϳ2-fold vs. 4 -5-fold, Table 1), which may again indicate immaturity.…”
Section: Tissue Engineering To Model (Human) Heart Tissue Functioncontrasting
confidence: 38%
“…In the case of the ventricular myocardium of rats (reviewed by Shigenobu, 1990), a tenfold decrease in the sensitivity to NA and isoprenaline occurs in the early postnatal period concurrently with the increase in sympathetic innervation density (Shigenobu et al, 1988;Tanaka & Shigenobu, 1990a). Sympathetic denervation studies (Ishii et al, 1982;Goto et al, 1985) and organ culture experiments (Tanaka et al, 1988a;Tanaka & Shigenobu, 1990b) revealed that sympathetic innervation is not only responsible for the pre-junctional component of the decreased sensitivity, but also exerts a long-term influence on myocardial properties to maintain the sensitivity to agonists at normal level. Whether the developmental decrease in sensitivity of the P-adrenoceptor-mediated effects (Tanaka et al, 1994) and conversion of o-adrenoceptor-mediated effects from positive to negative (Figure 1) Osnes et al, 1985), in hypoxia (Heathers et al, 1988), hypertension (Limas & Limas, 1987) and experimentally induced diabetes mellitus (Heijnis & van Zwieten, 1992).…”
Section: Discussionmentioning
confidence: 99%
“…Sympathetic innervation of the newborn heart modulates P-adrenoceptor number and function [7,28] presumably by downregulat ing receptor number through norepinephrine release. Alterations in the development of in nervation in the heart of the newborn rat by blocking nerve growth with antibody to nerve growth factor [14, 32] or 6-hydroxydopa [33] alter the normal postnatal changes in P-adrenoceptors.…”
Section: Receptor Density and Affinitymentioning
confidence: 99%